A paradigm of dynamic bargaining game based study on the salary of the private enterprises. Issue 4 (19th May 2017) - Jin, Cheng-Lin; Zhang, De-Yuan; Chen, Ting; Lu, Ke-Bin
Abstract: Nowadays, it is obvious that the number of the employees as well as the average salary is increasing both in stated-owned and private enterprises. However, the income gap of their staff expands gradually. Meanwhile, compared with the contribution which the private enterprises' employees have made, they haven't benefit from the rapid economic development. This study tries to find the causes of the income lag of the employees between the states-owned and private enterprises, to focus on the process of the bargaining game between the both sides of the private enterprises, to discuss the bargaining power of workers based on the model of dynamic bargaining game paradigm, to find the main factors which influence the final equilibrium wage, and finally puts forward some countermeasures based on the paradigm of dynamic bargaining game. This study shows that the employees' income amount in private enterprises is strongly associated with VL, Vb and. And this study is of rea σ C, σ L listic significance to provide an exoteric research approach and improve the workers' bargaining power.